2023
DOI: 10.3390/jcm12041564
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Medial Gastrocnemius Muscle Growth in Ambulant Children with Spastic Cerebral Palsy: A Prospective Longitudinal Study

Abstract: Only cross-sectional studies have demonstrated muscle deficits in children with spastic cerebral palsy (SCP). The impact of gross motor functional limitations on altered muscle growth remains unclear. This prospective longitudinal study modelled morphological muscle growth in 87 children with SCP (age range 6 months to 11 years, Gross Motor Function Classification System [GMFCS] level I/II/III = 47/22/18). Ultrasound assessments were performed during 2-year follow-up and repeated for a minimal interval of 6 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…This may be explained by the altered internal muscle architecture, containing declined muscle thickness, 20,21 muscle length, 22 cross‐sectional area, 20,23 muscle volume, 22,24 and fascicle length 20,21,24 . These abnormal alternations of muscle architecture are associated with altered muscle growth 25 . Besides, some muscle architecture alterations, such as the decreased volume of medial gastrocnemius and semitendinosus and the shorter medial gastrocnemius, can be more noticeable during low‐velocity stretches 26 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…This may be explained by the altered internal muscle architecture, containing declined muscle thickness, 20,21 muscle length, 22 cross‐sectional area, 20,23 muscle volume, 22,24 and fascicle length 20,21,24 . These abnormal alternations of muscle architecture are associated with altered muscle growth 25 . Besides, some muscle architecture alterations, such as the decreased volume of medial gastrocnemius and semitendinosus and the shorter medial gastrocnemius, can be more noticeable during low‐velocity stretches 26 .…”
Section: Introductionmentioning
confidence: 99%
“…When it comes to individuals with CP, numerous studies have applied ultrasound to assess muscle architecture over the past decade, 31–33,44–48 including muscle thickness, 20,21 muscle length, 22 cross‐sectional area, 20,23 muscle volume, 22,24 and fascicle length 20,21,24 . More recently, ultrasound has also been employed to monitor CP patients' muscle pathology from early age 25 . While many previous studies have investigated the reliability 20,21,32,44–49 and validity 31–33 of applying ultrasound to evaluate CP patients' muscle architectures, the findings have been inconsistent across different studies, making it difficult to draw a solid conclusion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Knowledge of growth rates in typically developing children may have implications for understanding disordered growth, for example, in children with neurological disorders such as cerebral palsy. Currently, it is largely unknown if growth rates differ between muscles, because most studies of muscle growth in childhood have investigated only one muscle (Bell et al, 2021;Benard et al, 2011;Binzoni et al, 2001;De Beukelaer et al, 2023;D'Souza et al, 2019;Herskind et al, 2016;Morse et al, 2008;Walhain et al, 2023;Weide et al, 2015Weide et al, , 2020 or a few muscles (Böl et al, 2017;Handsfield et al, 2022;Modlesky & Zhang, 2020;Mogi & Wakahara, 2022;O'Brien et al, 2010;Peeters et al, 2023;Siebert et al, 2017;Williams et al, 2022;Yanagisawa et al, 2014). O'Brien et al (2010) reported that the four components of the quadriceps muscles undergo similar relative increases in volume from childhood to adulthood.…”
Section: Introductionmentioning
confidence: 99%